Comparisons Between Successful Versus Unsuccessful Switches From Benzodiazepines or Zolpidem (Z-Drug) to Controlled-Release Melatonin in Patients With Major Depressive Disorder and Insomnia - An, Ji Hyun; Park, Mi Jin; Fava, Maurizio; Mischoulon, David; Kim, Hyewon; Jang, Jihoon; Hong, Jin Pyo; Park, Jun Sang; Jeon, Hong Jin (Frontiers in Psychiatry, 2020)
Objectives: Chronic use of benzodiazepines and zolpidem (BDZ/Z-drugs) leads to dependency, cognitive impairment, and falls. Although controlled-release melatonin (Melatonin CR) may be an alternative, a switch in clinical settings has proven difficult. We investigated the factors associated with successful switch to Melatonin CR in patients with major depressive disorder (MDD) and insomnia. Methods: This retrospective observational study involved 170 patients diagnosed with MDD and insomnia, and aged older than 55 years, who were treated with BDZ/Z-drug for at least the past 90 days and never before exposed to Melatonin CR. All patients were treated with a standard antidepressant therapy and Melatonin CR for their insomnia. A successful switch was defined as three or more consecutive prescriptions of Melatonin CR separated by at least one-month interval, after discontinuation of the BDZ/Z-drug. Results: Seventy-nine patients (46.5%) who switched successfully showed no significant differences in sex, age, education, and occupational status compared with the unsuccessful group. The types of antidepressants used or BDZ/Z-drug treatment did not differ significantly between the two groups. Fewer somatic symptoms were observed in the successful group. In the multivariate analysis, the successful group showed significantly less somatic anxiety, shorter duration from first BDZ/Z-drug use to the first antidepressant use, and shorter total duration of BDZ/Z-drug therapy. Conclusions: A successful switch from BDZ/Z-drug to Melatonin CR was associated with less baseline somatic anxiety, earlier use of antidepressants, and shorter total duration of BDZ/Z-drug use, but was less strongly associated with the type of antidepressants in MDD patients with insomnia.